1998
DOI: 10.1108/eb022530
|View full text |Cite
|
Sign up to set email alerts
|

Competitive asset or unnecessary expense? The role of the designer within UK fashion retailing

Abstract: While much is made of the contribution of design to the achievement of competitive advantage within the British fashion retail sector, little attempt has been made to examine the processes in which design is managed, integrated and developed within such companies. With the cooperation of 11 of the UK's most successful fashion retailers, this research identifies that the responsibility for design direction and development has moved from supplier to fashion retailer, in order that the latter can fully exploit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…According to Harris and de Chernatony (2001), there has been a shift in the brand literature from brand management which is consumer focused, to brand identity which focuses on how managers and employees make a brand unique. Additionally, a move towards globalisation, such as that which has occurred in fashion retailing (Moore and Shearer, 1998;Moore, 2000;Moore and Birtwistle, 2004) has led to a shift in emphasis from product brands to corporate brands as a communicator of corporate ideology and image (Aaker, 1996;Ind, 1997;de Chernatony, 1999;Aaker and Joachimstaler, 2000;Knox et al, 2000;Olins, 2000;Balmer, 2001;Harris and de Chernatony, 2001;Hatch and Schultz, 2003;Kapfer, 2004). It has been suggested that the development and implementation of own brand strategy is a vital element of retailer corporate strategy (Moore, 1995;Burt, 2000;Martensen, 2007), the range and type of own brands developed being directly related to the corporate brand image (Ailawadi and Keller, 2004).…”
Section: From Product Brand To Corporate Brandmentioning
confidence: 99%
“…According to Harris and de Chernatony (2001), there has been a shift in the brand literature from brand management which is consumer focused, to brand identity which focuses on how managers and employees make a brand unique. Additionally, a move towards globalisation, such as that which has occurred in fashion retailing (Moore and Shearer, 1998;Moore, 2000;Moore and Birtwistle, 2004) has led to a shift in emphasis from product brands to corporate brands as a communicator of corporate ideology and image (Aaker, 1996;Ind, 1997;de Chernatony, 1999;Aaker and Joachimstaler, 2000;Knox et al, 2000;Olins, 2000;Balmer, 2001;Harris and de Chernatony, 2001;Hatch and Schultz, 2003;Kapfer, 2004). It has been suggested that the development and implementation of own brand strategy is a vital element of retailer corporate strategy (Moore, 1995;Burt, 2000;Martensen, 2007), the range and type of own brands developed being directly related to the corporate brand image (Ailawadi and Keller, 2004).…”
Section: From Product Brand To Corporate Brandmentioning
confidence: 99%
“…Such a situation can merely exacerbate existing trends. Finally, quality‐based flexible specialization is not feasible for large segments of the industry that have neither the brand name to accompany such a shift nor the design (management, integration and development) capability to move into what is already a competitive niche market (Moore and Shearer, 1998). After all, there is only so much space for high fashion goods and the UK already has a strong market presence in this area.…”
Section: Discussionmentioning
confidence: 99%